Wireless Closed-Loop Optical Regulation System for Seizure Detection and Suppression In Vivo - Li, Yamin; Xu, Shengwei; Wang, Yang; Duan, Yiming; Jia, Qianli; Xie, Jingyu; Yang, Xiaowei; Wang, Yiding; Dai, Yuchuan; Yang, Gucheng; Yuan, Miao; Wu, Xiaoting; et al. (Frontiers in Nanotechnology, 2022)
There are approximately 50 million people with epilepsy worldwide, even about 25% of whom cannot be effectively controlled by drugs or surgical treatment. A wireless closed-loop system for epilepsy detection and suppression is proposed in this study. The system is composed of an implantable optrode, wireless recording, wireless energy supply, and a control module. The system can monitor brain electrical activity in real time. When seizures are recognized, the optrode will be turned on. The preset photosensitive caged compounds are activated to inhibit the seizure. When seizures are inhibited or end, the optrode is turned off. The method demonstrates a practical wireless closed-loop epilepsy therapy system.